Psikoedukasi Menguatkan Resiliensi Keluarga Dalam Merawat Pasien Skizofrenia di Puskesmas Gandus Palembang - Arisandy, Desy; Amanda Astri, Putri (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
This activity aims to evaluate the effectiveness of psychoeducation in strengthening the resilience of families caring for schizophrenia patients in the Gandus Palembang Health Center work area. The activity was carried out through a family-based psychoeducation approach, focusing on one of the patient's caregivers. The results of the implementation showed that, although in a limited scope and short time, providing psychoeducation empathetically and in context was able to provide a positive influence. Caregivers showed an increased understanding of the patient's condition, became calmer in facing the challenges of care, and had a higher awareness of the importance of the family's role in the recovery process of schizophrenia patients.